2020
DOI: 10.1617/s11527-020-01572-y
|View full text |Cite
|
Sign up to set email alerts
|

External strengthening of reinforced concrete beam with opening by bamboo fiber reinforced composites

Abstract: This paper presents the structural behaviour of reinforced concrete (RC) beams with and without openings strengthened externally with bamboo fiber reinforced composite (BFRC) plates in shear and flexure, respectively. Mechanical properties include tensile and flexural strength of epoxy, polyester and vinyl-ester based BFRC plates with 0%, 10%, 20%, 30% and 40% fiber volume fractions were evaluated. A total of fourteen beams were cast to evaluate the structural behaviour of RC beams strengthened with BFRC plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Hafizah et al [25] research also showed that retrofitting beams with natural fibers increases beam deflection and stiffness, which is similar to the findings by Chin et al [22]. This was confirmed by this research also, as deflections for the corroded retrofitted beams increased by 22% compared to the un-strengthened corroded beam.…”
Section: Comparisons To Parallel Researchsupporting
confidence: 88%
See 4 more Smart Citations
“…Hafizah et al [25] research also showed that retrofitting beams with natural fibers increases beam deflection and stiffness, which is similar to the findings by Chin et al [22]. This was confirmed by this research also, as deflections for the corroded retrofitted beams increased by 22% compared to the un-strengthened corroded beam.…”
Section: Comparisons To Parallel Researchsupporting
confidence: 88%
“…Bamboo as a reinforcing material is utilized in various forms such as mats, fibers, powder, and strips, with strips shown to have the better cohesive ability on structural members. Yet, most studies explore bamboo as a reinforcing material in retrofitting structural members, primarily as fibers [21,22] and few to none on strips. However, numerous studies covered bamboo fibers [31][32][33].…”
Section: Significance Of the Studymentioning
confidence: 99%
See 3 more Smart Citations